PENGGUNAAN KALIMAT IMPERATIF SEBAGAI MEDIA PROMOSI DALAM PENJUALAN ONLINE DI MEDIA SOSIAL TIKTOK - Utami, Annisa Tri; Ilmi Solihat; Agus Iryana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the forms of imperative sentences used as promotional media in online sales on TikTok social media and their implications for Indonesian language learning. This study uses a qualitative approach with a descriptive method. The data in this study are speech in live broadcasts and screen texts in promotional videos containing imperative sentences sourced from TikTok social media. The results of the study indicate that there are three forms of imperative sentences used in the context of speech and screen text in promotional videos, namely 32 actual imperative sentences, 13 prohibition imperative sentences, and 12 invitation imperative sentences. Actual imperative sentences are characterized by the use of command verbs, clear intonation, and the use of euphemisms. Prohibition imperative sentences are characterized by the use of prohibition markers. Meanwhile, invitation imperative sentences are characterized by invitation markers.